Cover Crop Management in a Chardonnay/99 Richter Vineyard in the Coastal Region, South Africa. 2. Effect of Different Cover Crops and Cover Crop Management Practices on Grapevine Performance - Fourie, J.C.; Louw, P.J.E.; Agenbag, G.A. (South African Journal of Enology and Viticulture, 2017)
The trial was conducted over a period of 10 years (1993/94 to 2002/03) on a medium textured soil in a Chardonnay/99 Richter vineyard near Stellenbosch (33°55’S, 18°52’E), situated in the Coastal Wine Grape Region of the Western Cape. Sixteen treatments, consisting of three grain species and five legumes, managed according to two cover crop management practices, were included. The one cover crop management practice consisted of cover crops being sown annually and full surface post-emergence chemical control being applied before bud break and when the berries reached pea size (BB). The other management practice consisted of cover crops being sown biennially and postemergence chemical control applied to the vine row before bud break and full surface when the berries reached pea size (AB). From 1999/2000 to 2002/03 the cover crops were sown annually, while the full surface post-emergence chemical control applied at the end of November was advanced to mid-October. These treatments were compared to a control, in which no cover crop was sown and the weeds were controlled mechanically in the work row and chemically in the vine row from bud break to harvest (approximately the first week of February). A treatment in which no cover crop was sown and full surface post-emergence chemical weed control was applied from before bud break to harvest (weedchem) was also included. During the 1994/95 season, the shoot mass of the two-year-old grapevines in the BB treatments was significantly higher than that of the control and the AB treatments. In the following season, the shoot mass and grape yield of the BB treatments was, with the exception of Vicia faba L. v. Fiord (faba bean) and Avena sativa L. v. Overberg, significantly higher than that of the control and weedchem. The grape yield of the control and AB treatments was significantly less than that of weedchem. Although significant differences in shoot mass (2000/01 and 2002/03) and grape yield (2002/03) were detected between treatments, no significant differences could be detected between the BB and AB treatments, with the exception of the shoot mass of Medicago scuttelata v. Kelson (‘Kelson’ medic). The mean petiole NO3-N concentration for the period 1994/95 to 1998/99 tended to be lower in the AB treatment of a cover crop species compared to that of the BB treatment of the same species. In the case of ‘Kelson’ medic (BB) the petiole NO3-N and juice N concentrations were significantly higher than that of the control and weedchem. The juice N concentration of the control and weedchem was significantly less than that of the faba bean treatments during 2000/01 and 2001/02, the Vicia dasycarpa Ten (grazing vetch) and ‘Kelson’ medic treatments during 2000/01, as well as that of Medicago truncatula Gaertn. (BB) and Trifolium subterraneum L. v. Woogenellup (BB) during the 2001/02 season. Wine quality did not differ between treatments.